Diagnosis of chronic endometritis: How many CD138+ cells/HPF in endometrial stroma affect pregnancy outcome of infertile women?. (24th November 2020) - Li, Yuye; Xu, Shiru; Yu, Shuyi; Huang, Chunyu; Lin, Shenglai; Chen, Wanru; Mo, Meilan; Lian, Ruochun; Diao, Lianghui; Ding, Lijun; Zeng, Yong
Abstract: Problem: The definition of chronic endometritis (CE) differs among studies, and currently, there is no accepted consensus. This study aimed to establish the minimum number of immunohistochemical analysis of CD138 + plasma cells to identify a clinically relevant CE. Method of study: We performed a retrospective study on 716 infertile patients who never did CE analysis and respective antibiotic treatment before. Samples were obtained by endometrial scratching in the mid‐luteal phase before IVF‐ET treatment. The number and distribution of CD138 + cells were analyzed by immunohistochemistry. Thirty high‐power fields (HPF) were evaluated for each sample. Patients were classified in 2 main groups: (a) CD138 low (<5 CD138 + cells in all HPFs), (b) CD138 high (≥5 CD138 + cells in at least one HPF). Pregnancy outcome was compared among the groups. Results: In the CD138 high group, β‐hCG positive rate, clinical pregnancy rate and live birth rate were significantly decreased ( P = .04, P = .01, P = .04, respectively). Also after adjusting for patient age, body mass index (BMI), and clinical characteristics, the β‐hCG positive rate ( P = .05), clinical pregnancy rate ( P = .01) and live birth rate ( P = .02) were significantly lower in the CD138 high than those in the CD138 low group. Within the CD138 low group, these parameters were not significantly different between patients without any plasma cells and patients with up to 4 plasma cells/HPF. Conclusion: We conclude that immunohistochemical analysis of CD138 + cells is a reliable method to detect CE which can be identified by the presence of ≥5 plasma cells in at least one out of 30 HPF.